Teachers’ Circumstances and Practices in Using Call (Computer Assisted Language Learning) in Indonesian Suburban Schools - Arfiyan Ridwan (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2016)
Nowadays, the integrated use of technology is inevitable in the digital world, including instructional process. The present study reports on the findings of English teachers teaching using CALL approach in suburban areas in Indonesia specifically in Bangkalan as one of the underdeveloped regencies in East Java province. From a total of 50 respondents across the regency, 25 English teachers from 15 schools responded intensively in answering the online questionnaire with closed-ended and open-ended questions. The researcher attempted to find out the teachers’ efficacy, the concrete form of CALL approach, and downsides when applying CALL during instructional process. The results indicated that in the digital era, those teachers already implemented CALL approach a simple manner despite limitations related to operational activities and facilities. Thus, this paper argues that the results of the research must be addressed with policies by the stakeholders that suburban teachers need to explore CALL approach more deeply as they are restricted merely in simple ways of CALL approach.